A Novel Ephemero- and a New CHeRI Orbivirus Isolated from a Dead Farmed White-Tailed Deer (Odocoileus virginianus) in Florida, USA - DeRuyter, Emily; Viadanna, Pedro H. O.; Wilson, Kristen; White, Zoe; Richardson, Amira; Urban, Merrie; Khrongsee, Pacharapong; Rodrigues, Thais C. S.; Waltzek, Thomas B.; Campos Krauer, Juan M.; Wisely, Samantha M.; Subramaniam, Kuttichantran; et al. (Viruses, 2025)
A novel ephemeral fever rhabdovirus and a CHeRI orbivirus of a previously unidentified genetic lineage were isolated in mosquito cell line C6/36 cells as co-infecting agents from the spleen tissue of a dead farmed white-tailed deer (WTD; Odocoileus virginianus) in Florida. We designated the ephemeral fever rhabdovirus as Hardee County ephemerovirus 1, strain CHeRI ephemerovirus 1. The genetic sequences of the CHeRI orbivirus isolated in this work differ significantly from those of three previously described CHeRI orbivirus lineages. We designated this new virus as CHeRI orbivirus 4, strain CHeRI orbivirus 4-1. Whereas it remains unknown whether one, both, or none of the viruses contributed to the pathology, gross observations revealed that the dead WTD had severely congested and hemorrhagic lungs, and that its heart, kidneys, and spleen were also congested.